2003
DOI: 10.1002/jmv.10386
|View full text |Cite
|
Sign up to set email alerts
|

Infantile viral gastroenteritis: On the way to closing the diagnostic gap

Abstract: A total of 305 faecal specimens collected from children under the age of 5 who presented with symptoms of acute gastroenteritis either as inpatients at Addenbrooke's Hospital (N = 100) or to General Practitioners in East Anglia (N = 205) during 1999-2001 were tested for the presence of rotavirus, norovirus, sapovirus, enteric adenoviruses (Group F, serotypes 40 and 41), and astrovirus. An aetiologic agent was found in 184 specimens (60.3%). The most commonly found single viral pathogen was rotavirus (27.9%), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
2
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 29 publications
(33 reference statements)
5
81
2
7
Order By: Relevance
“…Among the viruses, rotaviruses were by far the main cause of gastroenteritis in hospitalized children, far ahead of noroviruses, which were found in 8-15% of children hospitalized for gastroenteritis [8,25,[29][30][31]. These studies and our results contrast with other sentinel studies conducted by physicians in the general population [5,7,10], in which the incidence of norovirus ranged from 10 to 20%.…”
Section: Discussioncontrasting
confidence: 87%
“…Among the viruses, rotaviruses were by far the main cause of gastroenteritis in hospitalized children, far ahead of noroviruses, which were found in 8-15% of children hospitalized for gastroenteritis [8,25,[29][30][31]. These studies and our results contrast with other sentinel studies conducted by physicians in the general population [5,7,10], in which the incidence of norovirus ranged from 10 to 20%.…”
Section: Discussioncontrasting
confidence: 87%
“…Currently, norovirus (NoV) is thought to be responsible for 13-30% of episodes of viral gastroenteritis, particularly in hospitals or nursing homes. [1][2][3] As attempts to produce viral cultures have been unsuccessful, 4 development and assessment of diagnostic methods aimed at detecting norovirus have proven difficult and require electron microscopy or reverse-transcriptase polymerase chain reaction (RT-PCR), 5,6,8 for which specificity and sensitivity have been reported to be at 98.0% and 58.3% and 92.4% and 94.1%, respectively. 5 In 2001, an enzyme immunoassay (EIA) has become commercially available and is intended to facilitate diagnosis of this viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…Pang et al reported 20% and 9% detection rates for NVs and SVs, respectively, in stool specimens of children with acute gastroenteritis in Finland (31,32). It is generally accepted that SV gastroenteritis is less severe than that of rotavirus or NV; however, SVs have been detected in 1 to 3% of stool specimens collected from children hospitalized with gastroenteritis, indicating that SVs can cause severe illness (34,38,47). Also, with the increasing awareness of SV gastroenteritis and improved diagnostic methods, SVs were recently implicated in several gastroenteritis outbreaks in adult populations (22,43).…”
mentioning
confidence: 99%